Protective effect of baicalin on oxidative stress⁃induced apoptosis of gingival epithelial cells - ZHAO Shu⁃fan; CUI Ying⁃qiu (口腔疾病防治, 2016)
Objective To study the protective effect of baicalin on oxidative stress⁃ induced gingival epithelial cell apoptosisand its mechanism. Methods H2O2 was employed to form the oxidative stress ⁃ induced gingival epithelial cells apoptotic model, with the intervention of baicalin. The cell proliferation rate, cell apoptosis level, the protein ex⁃ pression of protein kinase B (Akt) and glycogen synthase kinase3β (GSK3β) were investigated respectively. Results Baicalin could effectively alleviate oxidative stress⁃induced inhibition of gingival epithelial cell proliferation and allevi⁃ ate apoptosis; and it could promote the phosphorylation of Akt⁃GSK3β signaling pathway. Conclusion Baicalin has a significant protective effect on oxidative stress⁃induced apoptosis of gingival epithelial cells, which may be related to the regulation of Akt⁃GSK3β signal pathway.